Design and Development of Construct 2-Based Learning Media for Teaching Three-Dimensional Geometry - Manaroinsong, Agnes Deviane; Domu, Ichdar; Laamena, Christina M. (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Game-based learning environments, in particular, offer enjoyable learning experiences while supporting the development of conceptual understanding. This study aims to develop and evaluate Construct 2–based learning media for teaching three-dimensional geometry in Grade 7. The research employed a Research and Development (R&D) design using the Akker model. Participants included media experts, material experts, and seventh-grade students from a public junior high school in Manado. The instruments used comprised expert validation sheets, student practicality questionnaires, and learning achievement tests. The development procedure involved identifying learning challenges related to students’ difficulties in visualizing geometric solids, designing the Construct 2 media, conducting expert validation, implementing one-to-one and small-group evaluations, and conducting a classroom field test. Data were analyzed descriptively to assess the validity, practicality, and effectiveness of the developed media. The findings indicate that the learning media achieved high validity based on evaluations from both media and material experts, high practicality based on students’ responses, and high effectiveness based on learning outcomes. The dynamic visualizations, interactive quizzes, and mobile accessibility offered by the media helped students overcome common difficulties in distinguishing and visualizing geometric solids and their nets. The novelty of this study lies in demonstrating the pedagogical value of Construct 2 not only as a feasible development tool but also as an effective instructional intervention. The study offers practical implications for educators seeking effective digital media for geometry instruction and provides a foundation for further innovation in game-based mathematics learning.